2019
DOI: 10.1017/jmech.2019.42
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Actuation Performance of Continuous Fiber Reinforced Piezoelectric Composite Actuator

Abstract: In this paper, a novel continuous fiber reinforced piezoelectric composite (CFRPC) actuator is proposed to improve the stability and reliability of piezoelectric actuators. A piezoelectric driving structure composed of a cantilever beam and the CFRPC actuator is utilized to research the actuation performance of the CFRPC actuator. The expression of the equivalent moment for the CFRPC actuator is obtained using the equivalent load method and electro-mechanical coupling theory. Based on Euler-Bernoulli beam theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Consequently, there has been extensive research regarding the development of actuators in the form of composites reinforced with piezoelectric fibers. 63 Dumoulin and Deraemaeker 62 explored the possibility of using composites with lead zirconate titanate (PZT) piezoelectric fibers as transducers (emitters and receivers) for monitoring concrete structures. The effective properties of piezoelectric composites were investigated using numerical and analytical models.…”
Section: Piezoelectric St Developments and Applicationsmentioning
confidence: 99%
“…Consequently, there has been extensive research regarding the development of actuators in the form of composites reinforced with piezoelectric fibers. 63 Dumoulin and Deraemaeker 62 explored the possibility of using composites with lead zirconate titanate (PZT) piezoelectric fibers as transducers (emitters and receivers) for monitoring concrete structures. The effective properties of piezoelectric composites were investigated using numerical and analytical models.…”
Section: Piezoelectric St Developments and Applicationsmentioning
confidence: 99%
“…Piezoelectric composites have excellent mechanical and electrical properties and have been increasingly used in piezoelectric actuators (Ma et al, 2019b). Consequently, numerous studies have been reported on the properties of piezoelectric composite actuators.…”
Section: Introductionmentioning
confidence: 99%